Importance of Facial Plastic Surgery Education in Residency: A Resident Survey - Curti, Steven A.; Jordan, J. Randall (International Archives of Otorhinolaryngology, 2020)
Introduction Facial plastic and reconstructive surgery (FPRS) is a key part of the curriculum for otolaryngology residents. It is important to gain an understanding of the breadth of exposure and level of competence residents feel with these concepts during their residency.Objective To determine the level of FPRS exposure and training otolaryngology residents receive during their residency.Methods A survey was emailed to all Accreditation Council for Graduate Medical Education (ACGME) accredited otolaryngology residents. The survey aimed to find the level of exposure to FPRS procedures otolaryngology residents get and how confident they feel with their training in cosmetic FPRS.Results A total of 213 residents responded to the survey for an overall response rate of 13.4%. There was an even mixture of residents from all postgraduate year (PGY) levels, with 58% of respondents being male. Almost all (98%) of the residents felt FPRS was important to otolaryngology residency training. Exposure to procedures varied with 57% performing or assisting with cosmetic minor procedures, 81% performing or assisting with cosmetic major procedures, and 93% performing or assisting with reconstructive procedures. Only 49% of residents felt their programs either very or somewhat adequately prepared them in cosmetic facial plastic surgery.Conclusion There was a wide variability in the FPRS procedure exposure. Most residents felt procedures were a vital part of otolaryngology residency training, but not all were able to participate in them. Only half of the residents felt well-prepared in cosmetic procedures.
Keywords: facial plastic surgery; residency; survey; education